Ajaran tentang Pembenaran menurut Paulus dan Yakobus, serta Signifikansinya bagi Pemahaman Soteriologis - Suyadi Tjhin (STT Iman Jakarta, 2021)
This article intends to provide Christian insight regarding the teachings of Paul's and James' justification, and its significance for Christian understanding. The main data of this research is literature study with qualitative methodology through Integrative Critical Analysis (ICA) approach, and descriptive exegesis analysis. The ICA's approach is carried out in connection with the many issues on this topic, for that it is analyzed according to context, doubted, justified, and looking for objectivity by referring to exegesis and descriptive Scripture. The results found by Paul and James are not contradictory, each writing is based on context, Paul writes because of the teachings (Judaism), James writes for Christians who claim to believe without deeds. Its significance is to remember that many Christians have non-Christian backgrounds before with the concept of salvation through good works; the existence of a church teaching salvation through faith plus spiritual gifts, sacraments, or rituals; a Christian person who knows salvation through faith but in certain circumstances doubts his salvation because of the feeling of the consequences of mistakes that occur in his life. AbstrakArtikel ini bermaksud memperlengkapi wawasan umat Kristiani berkenaan ajaran pembenaran Paulus maupun Yakobus, dan signifikannya bagi pemahaman umat Kristiani. Data utama penelitian ini ialah studi pustaka dengan metodologi kualitatif melalui pendekatan Integrative Critical Analysis (ICA), dan analisis deskriptif interpretatif. Pendekatan ICA dilaku-kan sehubungan banyaknya isu tentang topik ini, untuk itu dianalisis sesuai konteks, diragukan, dijustifikasi, dan mencari objektifitas dengan mengacu pada eksegesis dan deskripsi Alkitab. Hasil yang ditemukan Paulus dan Yakobus tidaklah kontradiktif, masing-masing menulis berdasarkan konteks, Paulus menulis karena adanya ajaran (Yudaisme), Yakobus menulis untuk umat Kristen yang mengklaim beriman tanpa adanya perbuatan. Signifikansinya ialah meng-ingat umat Kristiani banyak yang berlatarbelakang non Kristen sebelumnya dengan konsep keselamatan via perbuatan baik; adanya gereja mengajarkan keselamatan melalui iman plus karunia rohani, sakramen, atau ritual; pribadi umat Kristiani yang tahu keselamatan melalui iman namun dalam keadaan tertentu meragukan keselamatannya karena perasaan dari akibat kesalahan yang terjadi dalam hidupnya.